Periodontal disease in free‐ranging koalas (Phascolarctos cinereus) from the Mount Lofty Ranges, South Australia, and its association with koala retrovirus infection. Issue 5 (23rd January 2020) - Butcher, RG; Pettett, LM; Fabijan, J; Ebrahimie, E; Mohammadi‐Dehcheshmeh, M; Speight, KN; Boardman, WSJ; Bird, PS; Trott, DJ
Abstract : Background: In northern Australian koala populations (Queensland and New South Wales), periodontal disease (gingivitis and periodontitis) is common while koala retrovirus subtype A is endogenous, with other subtypes transmitted exogenously. Koala retrovirus has been hypothesised to cause immune suppression and may predispose koalas to diseases caused by concurrent infections. In southern Australia populations (Victoria and South Australia) periodontal disease has not been investigated, and koala retrovirus is presumably exogenously transmitted. This study described oral health in South Australian koalas and investigated if an association between periodontal disease and koala retrovirus exists. Methods: Oral health was examined for wild‐caught koalas from the Mount Lofty Ranges (n = 75). Koala retrovirus provirus was detected in whole blood using nested PCR and proviral load determined with qPCR. Periodontal disease severity was recorded and used to calculate the Final Oral Health Index (0‐normal, 24‐severe).Results Periodontal disease was observed in 84% (63/75) of koalas; 77% had gingivitis (58/75) and 65% (49/75) had periodontitis. The average Final Oral Health Index was 5.47 (s.d 3.13). Most cases of periodontal disease were associated with the incisors. Koala retrovirus‐infected koalas were more likely to present with periodontitis (p = 0.042) and the Final Oral Health Index was negatively correlated with proviral load (ρ = −0.353, p = 0.017). Conclusion: South Australian koalas had a high prevalence of gingivitis and periodontitis. Periodontal disease was more prevalent in the incisors. Exogenous koala retrovirus infection may also facilitate the development of periodontitis by modulation of the immune response to concurrent oral bacterial infections.